2004
DOI: 10.1007/bf02850034
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine effects of organophosphate antidotal therapy

Abstract: To determine the endocrine effects of the treatment of organophosphate poisoning, this prospective study was conducted in a university-based emergency department among patients with a history and clinical findings compatible with those of organophosphate poisoning. Thyrotrophin (TSH), free triiodothyronine (FT3), free thyroxine (FT4), follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), progesterone (PRG), adrenocorticotropic hormone (ACTH), cortisol, and testosterone (TST) levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…As regards serum cortisol level, this study revealed that median cortisol level at admission was 47.3μg/dl. This is partially similar to Satar, (2004) who reported median cortisol level at admission was 41.8μg/dl. Other studies as Güven et al, (1999) andDutta et al, (2015) reported that the mean cortisol level at admission was 25.5± 14 and 34.3 μg/dl respectively.…”
Section: Resultssupporting
confidence: 90%
“…As regards serum cortisol level, this study revealed that median cortisol level at admission was 47.3μg/dl. This is partially similar to Satar, (2004) who reported median cortisol level at admission was 41.8μg/dl. Other studies as Güven et al, (1999) andDutta et al, (2015) reported that the mean cortisol level at admission was 25.5± 14 and 34.3 μg/dl respectively.…”
Section: Resultssupporting
confidence: 90%
“…LH is secreted by the pituitary gland then induces Leydig cells to secrete testosterone. Many OPs were tested for their effect on plasma levels of testosterone (Blanco-Muñoz et al 2010;Satar et al 2004). In our experiment, introducing malathion for 4 weeks was associated with a reduction in plasma levels of testosterone.…”
Section: Discussionmentioning
confidence: 97%
“…Chronic exposure to organophosphate insecticides has been associated with neuropsychological conditions and has more recently been shown to have specific endocrine effects [5][6][7]. We are reporting the results of the effect of prolonged low-dose exposure to chlorpyrifos, an organophosphate insecticide, in young rats that gained weight.…”
Section: Introductionmentioning
confidence: 95%